Gestión de talento humano en la Hacienda D’Roma del cantón Vinces, periodo 2023. - Arévalo Salazar, Arturo Alfonso (2024)
This case study was developed at Hacienda D'Roma, located in the Vinces canton. The context of the research was on human talent management, as an important factor in the development of all types of companies. The objective of the research was to analyze the human talent management practices at Hacienda D'Roma in the Vinces canton during the period 2023, in order to identify how the different processes are executed, such as recruitment, selection, training and evaluation of personnel. The present work was based on a deductive method, which was descriptive and had a qualitative-quantitative approach. Among the results obtained, a notable lack of training programs stands out. Aspects such as the good work environment, as well as good relations between the administrative and agricultural areas, are highlighted. A negative factor is the informality of the recruitment and selection processes, in order to have suitable personnel in the positions. For this research, the research line of the Commerce Career was considered: Management, financial, administrative, tax, audit and control; as well as the research subline: Public and private companies and institutions.